MODELO DE PREDICCIÓN DEL INICIO DE LA SEQUÍA EN EL PERÚ USANDO EL INDICE DE VEGETACION PROCEDENTE DE IMÁGENES DE SATÉLITE E INDICES EL NIÑO OSCILACIÓN SUR - Rojas Acuña, Joel (2006)
El Niño Southern Oscillation (ENSO) indices and satellite-recorded Normalized Difference Vegetation Index (NDVI) will be used to construct a drought onset prediction model for North Coast of Peru through a multiple linear regression. Monthly NDVI and ENSO indices anomaly data for the period July 1981 to December 2003 were used to develop the model. The objective of the work, first part, is to do a description of how and where the data are obtained and it does calculate their anomalies. NDVI anomaly time series, in the period 1981-2003 were compared with El Niño Southern Oscillation (ENSO) indices. A visual inspection of the anomalies plot shows a correlation in the 82-83 and 97-98 Niños. NDVI of the Loreto region in the jungle of Peru doesn’t show any change in relation to ENSO indixs.